Para além dos fios : cabelo crespo e identidade negra feminina na contemporaneidade - Santos, Denise Bispo dos (2019)
The present research aims to understand the phenomena that led a group of black women to assume afro curly hair making it an expression of the struggle against racism, a resistance strategy and a redefinition of contemporary black feminine identity. In this sense, in order to understand the influence of hair on the subjectivity of these women, four hair paradigms were analyzed: Hair Straightening, Capillary Plurality, Black Power and Hair Transition. Through contributions from the field of History of the Present Time that provides us with possibilities to analyze the movement of social subjects around the capillary aspect in contemporary times, the data was collected through the magazines “Raça Brasil”, narratives of women from the cities of Aracaju / SE and Salvador / BA and reports of groups in virtual networks. With regard to the results found, this capillary return is inflected to multiple dimensions such as dialogue with the female body, affirmation of identity, insurgency of a virtual and face-to-face movement around the capillary issue, as well as exchange of experiences which are intensely loaded with subjectivity, a fundamental prism for the ways in which the women acquired meanings in the current context. In this way, the present research seeks to contribute with a reflection on the construction of the identity of women who experience and create a resignification of the capillary representations based on the intense relation with the paradigms that revolve around afro curly hair.